Spectra Comparison For An Optical Breathing Gas Sensor Development - Nurulain, S.; M. R., Radin; K., Suzalina; Hadi, Manap (AIP Publishing, 2017)
This paper describes a preliminary study of the possibility for inhaled and exhaled gases interference during Methyl Mercaptan measurement in the 200 nm - 250 nm region. An absorption spectrum for Methyl Mercaptan was compared with the breathing system gases absorption lines to theoretically justify that there are no discernible interference effects during the Methyl Mercaptan concentration measurements. It was theoretically found that the primary breathing gases namely nitrogen, oxygen, carbon dioxide and water vapor have no significant interference for Methyl Mercaptan sensing in the 200 nm - 250 nm region.